Complications of Acute Coronary Syndrome in Young Patients - Che' Muda CHE-MUZAINI; Bachok NORSA'ADAH (Tehran University of Medical Sciences, 2017)
Please provide alternate text for this image to ensure accessibility for users with text-only browsers or assistive devices